Effect of Nutrition Education Intervention to Diabetic Subjects on use of Millet Recipes in the Management of Diabetes (Indian Journal of Extension Education, 2019)
Diabetes mellitus is the most common metabolic disorder affecting humankind and creating health hazard. The inclusion of millets in the diabetic diet has been reported from ancient days in India as they exhibit hypoglycaemic effect due to presence of higher proportion of complex carbohydrate, resistant starch, slow rising sugars and water-soluble gum β-glucans. With this context the study was conducted in which the knowledge, attitude and practice of millets of the diabetic subjects were seen and further the intervention programme on consumption of millet recipes for 30 days was conducted on 12 diabetic volunteers. The nutrition education enhanced the level of adoption of millets by12.9 per cent. Significant reduction in Fasting and Post Prandial Blood sugar level and reduction in diabetic symptoms were also observed. Millet recipes along with the recommendation for diabetics can also be introduced in the regular diet of normal healthy people which in return may help to increase the food value chain of millets.